Peran Tenaga Kesehatan, Promosi Kesehatan dan Dukungan Keluarga Terhadap Pencegahan Anemia pada Ibu Hamil - Madinah Munawaroh; Pinna PN Situmorang (SIMFISIS Jurnal Kebidanan Indonesia, 2021)
Introduction: Anemia is one of the most common nutritional disorders during pregnancy, this anemia can be achieved with iron supplementation. Pregnant women who suffer from severe anemia can increase the risk of maternal and infant morbidity and mortality, the possibility of giving birth to babies with low birth weight. Objectives: The purpose of the study was to determine the relationship between health promotion, the role of health workers, and family support with the prevention of anemia in pregnant women in the working area of ​​the Bondongan Health Center, Bogor City in 2019. Method: This type of research, quantitative and analytical descriptive approach using the cross-sectional method. The study population was all pregnant women as many as 128 people and a sample of 56 respondents. The sampling technique is purposive sampling. The measuring instrument uses a questionnaire. Data analysis using chi-square with 0.05. Result: The results showed that the prevention of anemia in pregnant women was in the poor category (57%), the role of health workers was not good (55%), health promotion was not good (63%), low family support (54%) in preventing anemia in pregnant women working area of ​​Bondongan Health Center, Bogor City in 2019. Conclution: There is a significant relationship between the role of health workers (P-value 0.04), Health Promotion (P-value 0.012), and Family Support (P-value 0.02) on the prevention of anemia in pregnant mothers.